The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1063/1.4866382
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and magnetic properties of size-tunable MnxFe3−xO4 ferrite nanoclusters

Abstract: We report the synthesis and characterization of size-tunable MnxFe3−xO4 ferrite nanoclusters of different sizes ranging from ∼30 to ∼120 nm. The nanoclusters synthesized via a hydrothermal polyol process show high crystallinity and a narrow size distribution. The magnetic properties of the nanoclusters demonstrate well-behaved magnetization and low-coercivity characteristics, ferrimagnetically at a large size, and superparamagnetically at a small size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…From a structural point of view, the introduction of Mn determines a decrease in size of both the nanoclusters and the primary nanocrystals, which is reflected in the variations observed in saturation magnetisation: for lower doping regimes (0 o x o 0.5) the net magnetisation is increased due to the Mn contribution, while for higher doping regimes (x Z 0.5) the effects of size reduction prevail and cause its overall decrease. 28,32 Thus, our choice of introducing a low Mn doping content is intended as a conservative approach to boost the net magnetisation without heavily affecting the size of the nanocrystals and nanoclusters. In order to assess the effect of Mn-doping on our clusters, the DC magnetic susceptibility was measured as a function of temperature at low fields according to the ZFC-FC (Zero-Field Cooled-Field Cooled) protocols, while isothermal hysteresis loops were recorded at 5 K and body temperature (310 K).…”
Section: Magnetic Structure Of the Mn-doped Iron Oxide Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…From a structural point of view, the introduction of Mn determines a decrease in size of both the nanoclusters and the primary nanocrystals, which is reflected in the variations observed in saturation magnetisation: for lower doping regimes (0 o x o 0.5) the net magnetisation is increased due to the Mn contribution, while for higher doping regimes (x Z 0.5) the effects of size reduction prevail and cause its overall decrease. 28,32 Thus, our choice of introducing a low Mn doping content is intended as a conservative approach to boost the net magnetisation without heavily affecting the size of the nanocrystals and nanoclusters. In order to assess the effect of Mn-doping on our clusters, the DC magnetic susceptibility was measured as a function of temperature at low fields according to the ZFC-FC (Zero-Field Cooled-Field Cooled) protocols, while isothermal hysteresis loops were recorded at 5 K and body temperature (310 K).…”
Section: Magnetic Structure Of the Mn-doped Iron Oxide Clustersmentioning
confidence: 99%
“…Although the doping of the clusters can occur during an easy step of one-pot, rapid chemical synthesis, only few cases of relevant preliminary chemical studies have been reported so far. 28,29 In our experiments, Mn-doped iron oxide CNCs have been prepared and evaluated as MRI contrast agents as well as heating probes in magnetic fluid hyperthermia. These nanomaterials may hold a great potential for biomedical applications and highlight the need of more synthetic efforts to enrich the library of functional doped-CNCs.…”
Section: Introductionmentioning
confidence: 99%
“…25 The peak shift is accompanied with a lattice expansion (Table S1), indicating the successful incorporation of Zn 2+ and Mn 2+ ions into the γ-Fe2O3 crystal lattice. 23,35 Furthermore, no diffraction peaks corresponding to pure zinc oxide or manganese oxide were observed. The average crystallite size (dXRD) was about 14 nm for both γ-Fe2O3 and Zn0.5Fe2.5O4 and 18 nm for Mn0.5Fe2.5O4 (Figure 2a).…”
Section: Resultsmentioning
confidence: 98%
“…The magnetic saturation value is increased with increasing cluster size effects. 31 Both FT-IR and NMR spectra show that corresponding results of the modification of PCMNCs. The original form of polysorbate 80 contains a CO stretching vibration band at 1735 cm −1 , which is slightly shifted to 1733 cm −1 for the modified form; this is due to the presence of negatively charged tricarboxylate groups on the PCMNCs (Figure 2D).…”
mentioning
confidence: 99%
“…The magnetic hysteresis loop of MNPs and PCMNCs were analyzed using a vibration sample magnetometer at 298 K. The magnetic saturation values at 15T are measured to be 67.7 and 68.3 emu g –1 for MNPs and PCMNCs, respectively (Figure S3). The magnetic saturation value is increased with increasing cluster size effects . Both FT-IR and NMR spectra show that corresponding results of the modification of PCMNCs.…”
mentioning
confidence: 99%